2005
DOI: 10.1071/bt04131
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of clonality and limited sexual reproduction in the endangered shrub Acanthocladium dockeri (Asteraceae)

Abstract: Allozyme electrophoresis was used to determine the extent of clonality in four naturally occurring populations of Acanthocladium dockeri F.Muell. from the mid-north of South Australia. A total of 33 loci was scored for at least 16 plants from each population. The four known populations of A. dockeri represent four quite distinct genetic clones. Each natural population consists of a single genet, and no indication of any correlation between geographical proximity and genetic similarity was found. Seed set in fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…This can range from reduced seed set in populations with fewer clones, as in Dithyrea maritima (Aigner 2004), to apparent complete loss of sexual reproduction. Several rare Australian species persist as a single clone per population with no known sexual reproduction: Santalum lanceolatum (Warburton et al 2000), Grevillea infecunda (Kimpton et al 2002), Borya mirabilis (Coates et al 2002) and Acanthocladium dockeri (Jusaitis and Adams 2005). While Ziziphus celata has not reached these extremes, fruit set in the wild is extremely limited even in multiclonal populations, and seedlings have never been recorded despite yearly monitoring (Ellis et al 2007;Weekley unpublished data).…”
Section: Discussionmentioning
confidence: 94%
“…This can range from reduced seed set in populations with fewer clones, as in Dithyrea maritima (Aigner 2004), to apparent complete loss of sexual reproduction. Several rare Australian species persist as a single clone per population with no known sexual reproduction: Santalum lanceolatum (Warburton et al 2000), Grevillea infecunda (Kimpton et al 2002), Borya mirabilis (Coates et al 2002) and Acanthocladium dockeri (Jusaitis and Adams 2005). While Ziziphus celata has not reached these extremes, fruit set in the wild is extremely limited even in multiclonal populations, and seedlings have never been recorded despite yearly monitoring (Ellis et al 2007;Weekley unpublished data).…”
Section: Discussionmentioning
confidence: 94%
“…limitanea seedlings with a height of c. 3-5 cm. This pilot study demonstrated the presence of suitable allozyme markers in seedling homogenates prepared using the homogenisation and sample treatment methods of Jusaitis & Adams (2005) developed for live cuttings of the endangered plant Acanthocladium dockeri. These methods were adopted for all subsequent screens.…”
Section: Methods Sampling For Electrophoresismentioning
confidence: 99%
“…The following enzymes displayed sufficient activity and resolution to allow genetic interpretation: ACON, ACP, AdH, Ald, ENOl, fdP, GAPd, GdH, GOT, GPi, GPT, GSR, Hk, idH, lAP, MdH, ME, NdPk, PEP-B, PGAM, 6PGd, PGk, PGM, TPi, and UGPP. details of enzyme and locus abbreviations, enzyme commission numbers, electrophoretic conditions, and stain recipes are presented in Richardson et al (1986) or Jusaitis & Adams (2005). All wild plants sampled were genotyped using leaf tissue.…”
Section: Methods Sampling For Electrophoresismentioning
confidence: 99%
“…Genetic erosion is the reduction in effective population size within a population over time; where infrequently occurring alleles are likely to be lost, further hindering population survival by reducing adaptive potential (van Treuren et al 1991). In addition, populations an important representative of Australian botanical diversity (Jusaitis and Adams 2005;Clarke et al 2013;Bickerton et al 2018). Only six small pop Clarke et al 2013ulations (~ 87-1986 ) are known to occur within the mid-north of South Australia and are separated by 4-110 km distances.…”
Section: Introductionmentioning
confidence: 99%